Self-Powered, Room Temperature Electronic Nose Based on Triboelectrification and Heterogeneous Catalytic Reaction - Kim, Ji-hyun; Chun, Jinsung; Kim, Jin Woong; Choi, Won Jun; Baik, Jeong Min (WILEY-V C H VERLAG GMBH, 2015)
Herein, a self-powered electronic nose strategy with highly selective gas detection is described. The electronic nose is a two-dimensional microarray based on the triboelectrification between ZnO nanowires and the dielectric layers, and the heterogeneous catalytic reaction occurring on the nanowires and on the NiO nanoparticles. These electronic noses show the ability to distinguish between four volatile organic compound (VOC) gases (methanol, ethanol, acetone, and toluene) with a detection limit of 0.1% at room temperature using no external power source.